Synthesis of Cephalosporin C from Sulfate by Mutants of Cephalosporium acremonium - Niss, H. F. (1973)
The innate ability of Cephalosporium acremonium to use methionine preferentially over sulfate for synthesis of cephalosporin C can be influenced through mutation. Mutants of C. acremonium with altered capacity to utilize sulfate for synthesis of antibiotic were isolated and partially characterized with respect to the uptake of sulfate and the regulation of arylsulfatase.